Factors Affecting Community Participation in Paying Land and Building Tax in Kuningan Regency - Amir Hamzah; Anisa Laila Rahayu; Hasna Firyal Khaerunnisa; Riska Riska; Dzikro Hillyatul Aulia (Jambura Equilibrium Journal, 2023)
The main purpose of this study is to find out the factors that influence community participation in paying Land and Building Tax to communities in Kuningan Regency. This study used descriptive and verifiable methods. The sample in this study was 400 respondents. Based on the results of the study that tax literacy, community attitudes, and the leadership of the village head have a joint influence on community participation in paying land and building taxes, partially tax literacy has a significant positive effect on community participation in paying land and building taxes, community attitudes have a significant positive effect on community participation in paying land and building taxes, and the leadership of the village head has a significant positive effect on community participation in paying land and building taxes.